Dynamically Sublime, Vision, and Image in Architecture. The Relationship between 3D Graphics and Physiology of Vision in the Construction of Rendering Images - Cristian Farinella; Lorena Greco (Proceedings, 2017)
The construction of digital images and the role of the CG Artist in communicating architectural projects establishes its origin in pictorial tradition and visual arts. The text focuses on some aspects of this cultural legacy and makes a comparison using biometric instruments, now able to validate and compare the sensibility of the “creator” artist with the perception of sublime of the observer. Understanding the foundations that guide vision and perception of space, whether it is bidimensional or real, is relevant to all disciplines, primarily the architectural one, for the production of computer images.